2020
DOI: 10.1039/d0cp03102j
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy redistribution during donor–acceptor electronic energy transfer: criteria to identify subsets of active normal modes

Abstract: Photoinduced electronic energy transfer in conjugated donor-acceptor systems is naturally accompanied by intramolecular vibrational energy redistributions accepting an excess of electronic energy. Herein, we simulate these processes in a covalently...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Nevertheless, there is cumulative evidence that the vibrational energy redistribution in the direction of the nonadiabatic coupling vector may play a bigger role than usually expected. Fernandez-Alberti, Tretiak, and co-workers have shown for several classes of systems that the vibrational energy relaxation after a nonadiabatic transition is biased toward the nonadiabatic coupling vector’s direction. Their analysis of vibrational energy redistribution revealed that only a small subset of normal modes with large overlap with the nonadiabatic coupling vector actively contributes to the electronic relaxation process. Sellner and co-workers have also shown that the exit direction from the conical intersection may be the main driver for forming specific photoproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is cumulative evidence that the vibrational energy redistribution in the direction of the nonadiabatic coupling vector may play a bigger role than usually expected. Fernandez-Alberti, Tretiak, and co-workers have shown for several classes of systems that the vibrational energy relaxation after a nonadiabatic transition is biased toward the nonadiabatic coupling vector’s direction. Their analysis of vibrational energy redistribution revealed that only a small subset of normal modes with large overlap with the nonadiabatic coupling vector actively contributes to the electronic relaxation process. Sellner and co-workers have also shown that the exit direction from the conical intersection may be the main driver for forming specific photoproducts.…”
Section: Introductionmentioning
confidence: 99%
“…21 There have been reports of IVR that is slightly faster in a set of small amides in aqueous solution (4.9 ps for N-methylacetamide), 22 and a simulation study even propose IVR that is concomitant with the electronic transition. 23 The latter has not be experimentally verified so altogether 10 ps is a good ballpark number. The concept of IVR is a fairly theoretical approach to experimental femtochemistry, but herein it is assumed that it is a sensible vantage point for the description of molecular dynamics.…”
Section: ψ ⟩mentioning
confidence: 99%
“…The process of distributing the vibrational energy to the vibrational states that were not included in the formation of the original wave packet is referred to as intramolecular vibrational redistribution (IVR); the time scale involved is debatable and strongly dependent on the system (primarily rigidity and symmetry), but the consensus is that >10 ps is not too far off . There have been reports of IVR that is slightly faster in a set of small amides in aqueous solution (4.9 ps for N -methylacetamide), and a simulation study even propose IVR that is concomitant with the electronic transition . The latter has not be experimentally verified so altogether 10 ps is a good ballpark number.…”
Section: Introductionmentioning
confidence: 99%
“…One final comment is that the vibrational mode identities in such a complex system containing TbAcI and the quencher are generally not preserved during electronic dynamics because of normal mode mixing. [43]…”
Section: F I G U R Ementioning
confidence: 99%